2018
DOI: 10.7717/peerj.5797
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment ofPocillopora verrucosa(Scleractinia; Pocilloporidae) distribution along a depth gradient in Ludao, Taiwan

Abstract: It can be challenging to identify scleractinian corals from the genus Pocillopora Lamarck 1816 in the field because of their large range of inter- and intra-specific morphological variation that co-occur with changes in the physical environment. This task is made more arduous in the context of a depth gradient, where light and water current could greatly affect the morphology of the corallum. Pocillopora verrucosa (Ellis & Solander 1786) in Taiwan was previously reported exclusively from shallow waters (<10 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…P. verrucosa is widely distributed and is prevalent in the Red Sea, across the Indian Ocean, and across the Pacific Ocean, up to the Eastern Tropical Pacific, colonizing an extensive range of depths that cover shallow to mesophotic settings ( Schmidt-Roach et al. 2014 ; De Palmas et al. 2018 ; Soto et al.…”
Section: Introductionmentioning
confidence: 99%
“…P. verrucosa is widely distributed and is prevalent in the Red Sea, across the Indian Ocean, and across the Pacific Ocean, up to the Eastern Tropical Pacific, colonizing an extensive range of depths that cover shallow to mesophotic settings ( Schmidt-Roach et al. 2014 ; De Palmas et al. 2018 ; Soto et al.…”
Section: Introductionmentioning
confidence: 99%
“…Effective ecological connectivity between shallow and deep zonations is achieved under three prerequisite criteria: 1) suitable habitats supporting robust populations, 2) habitats that are physically connected via water or propagule movements, and 3) organisms with life-history traits that enable successful replenishment of both their own populations and those connected to them [ 45 ]. In Ludao, Denis et al [ 48 ] and De Palmas et al [ 50 ] reported that P . verrucosa is one of the dominant species found across the depth gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-five colonies originating from three depth ranges—Shallow (7–15 m, hereafter “S”), Mid-depth (23–30 m, hereafter “M”), and Deep (38–45 m, hereafter “D”)—were previously confirmed to be Pocillopora verrucosa by mtORF sequencing [ 50 ]. Nine locations were defined accordingly: Gongguan S, Gongguan M, Gongguan D, Guiwan S, Guiwan M, Guiwan D, Dabaisha S, Dabaisha M, and Dabaisha D. Locations are separated by vertical distances (i.e., depth) and horizontal distances (i.e., perpendicular to the depth axis) so that the frontal distances between locations from the same site are < 100 m.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations